2007
DOI: 10.1016/j.ejcts.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Is the Allen test reliable enough?

Abstract: The Allen test is a good and valid screening test for the circulation of the hand. If the Allen test is negative it is safe to harvest the radial artery. If it is positive further examinations are needed to ensure safe harvesting of the radial artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 10 publications
4
56
1
3
Order By: Relevance
“…Traditionally and widely, this has been done with MAT, 8 which is cheap, rapid and simple. Nevertheless, the MAT has been criticized 16,17 for being too unreliable and subjective, and for its relatively low sensitivity and specificity. Approximately 17% our patients had positive MAT.…”
Section: Discussion Preoperative Screening and Doppler Ultrasonographmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally and widely, this has been done with MAT, 8 which is cheap, rapid and simple. Nevertheless, the MAT has been criticized 16,17 for being too unreliable and subjective, and for its relatively low sensitivity and specificity. Approximately 17% our patients had positive MAT.…”
Section: Discussion Preoperative Screening and Doppler Ultrasonographmentioning
confidence: 99%
“…other studies. 8,16,17 Doppler ultrasonography of RA allows for the evaluation of adequacy of the ulnar collateral circulation to the hand and also allows for the preoperative rejection of an RA graft with poor quality such as small diameter, vessel wall arteriosclerosis, or calcification to be recognised. There was positive result for the MAT in 17.3% of patients in our study.…”
Section: Discussion Preoperative Screening and Doppler Ultrasonographmentioning
confidence: 99%
“…Various techniques can be used either alone or in combination. In light of our earlier studies we recommend the use of ultrasonography in selected patients (5). Occasionally, the only preoperative screening method available is the Allen test.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we studied the quality of radial arteries planned to be harvested and also determined the optimal preoperative assessment routine to select appropriate patients for radial harvesting (5). We found that severe complications are rare, with careful screening, most likely avoidable.…”
mentioning
confidence: 99%
“…We read with great interest the article by Kohonen et al [1] dealing with the diagnostic role of the Allen test in the evaluation of hand circulation. We congratulate the authors for their study.…”
mentioning
confidence: 99%